REPUTASI AUDITOR SEBAGAI PEMODERASI PENGARUH KEPEMILIKAN MANAJERIAL TERHADAP MANAJEMEN LABA - Adi Sukayana, Gede; Pradnyantha Wirasedana, I Wayan (E-Jurnal Akuntansi; Vol 15 No 2 (2016), 2016)
Profit is one of the most risky components as the basis for the decision making of its stakeholders. Earnings information is often used as opportunistic actions resulting asymmetry of information. The purpose of this study was to examine the effect of managerial ownership on earnings management and the ability to moderate the effect of auditor reputation of managerial ownership on earnings management. Sampling of this research is purposive sampling technique. The research sample is manufacturing companies listed in Indonesia Stock Exchange from 2010-2014, as many as 14 companies. The data analysis technique used is the technique of regression analysis of the moderation or moderated regression analysis. Based on the research that has been done, the first hypothesis testing results prove that managerial ownership negatively affect earnings management. Results of testing the hypothesis of two results where the auditor's reputation as a moderating variable can not moderate the managerial ownership on earnings management.
Keywords: Auditor Reputation, Managerial Ownership, Earnings Management